2015
DOI: 10.1177/0956797615618365
|View full text |Cite
|
Sign up to set email alerts
|

Variation in an Iron Metabolism Gene Moderates the Association Between Blood Lead Levels and Attention-Deficit/Hyperactivity Disorder in Children

Abstract: Although attention-deficit/hyperactivity disorder (ADHD) is a heritable neurodevelopmental condition, there is also considerable scientific and public interest in environmental modulators of its etiology. Exposure to neurotoxins is one potential source of perturbation of neural, and hence psychological, development. Exposure to lead in particular has been widely investigated and is correlated with neurodevelopmental outcomes, including ADHD. To investigate whether this effect is likely to be causal, we used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 52 publications
0
22
1
Order By: Relevance
“…Nevertheless, a recent genome-wide association study of sensitivity to lead exposure in fruit flies also has found pronounced sex differences, such that none of the genes that conferred sensitivity to lead on activity level in females were overlapping with those identified in males (Zhou et al, 2016). Note that the interaction between C282Y and blood lead level was not a significant predictor of children's symptoms of conduct disorder and oppositional defiant disorder in this study (Nigg et al, 2016).…”
Section: Potential Moderators Of Lead Exposurecontrasting
confidence: 65%
See 2 more Smart Citations
“…Nevertheless, a recent genome-wide association study of sensitivity to lead exposure in fruit flies also has found pronounced sex differences, such that none of the genes that conferred sensitivity to lead on activity level in females were overlapping with those identified in males (Zhou et al, 2016). Note that the interaction between C282Y and blood lead level was not a significant predictor of children's symptoms of conduct disorder and oppositional defiant disorder in this study (Nigg et al, 2016).…”
Section: Potential Moderators Of Lead Exposurecontrasting
confidence: 65%
“…Thus, in HFE , a change from cysteine to thymine at amino acid position 282 (C282Y) and from histidine to aspartic acid at amino position 63 (H63D) causes a shortage of the HFE protein and, ultimately, increased iron uptake in the gut (Hanson, Imperatore, & Burke, ). Consistent with the likelihood that individuals who carry the C282Y mutations absorb more lead do than wild‐type carriers, lead exposure in the normal range was more strongly associated with symptoms of hyperactivity‐impulsivity according to parents and teachers for youth (6‐ to 17‐year‐olds) who carried the mutation than for youth who carried the wild‐type version of the gene (Nigg, Elmore, Natarajan, Friderici, & Nikolas, ). This interaction effect was detected more reliably in boys than in girls, although the sample of girls was smaller than that of boys (Nigg et al., ).…”
Section: Potential Moderators Of Lead Exposurementioning
confidence: 77%
See 1 more Smart Citation
“…At the morphological level, prenatal lead exposure delays structural development of the fetal cortex (Bull, McCauley, Taylor, & Croften, 1983), and affects differentiation and synaptogenesis (Regan, 1989). Although it is more difficult to study potentially causal mechanisms in human studies, Mendelian randomization as mentioned earlier lends further weight to the causal evidence linking lead exposure to neurobehavioral outcomes in children (Nigg, Elmore, Natarajan, Friderici, & Nikolas, 2016).…”
Section: Vulnerability Of Children To Leadmentioning
confidence: 99%
“…Nigg et al (in press) reported that child genotype on the HFE gene (human hemochromatosis protein gene; 6p22.2) moderated the strength of association of children’s blood lead level with their teacher-rated hyperactivity symptoms. This was observed at blood lead levels that are typical in the U.S. population (about 1ug/dL), suggesting these effects may be widespread.…”
Section: Synthesis: a Testable Paradigm?mentioning
confidence: 99%